Efektivitas Sistem Aplikasi Elektronik BUMDes Sugihwaras (e-BES) dalam Pengelolaan Badan Usaha Milik Desa (BUMDes) di Desa Sugihwaras Kecamatan Candi Kabupaten Sidoarjo - Nur Febrianti; Eva Hany Fanida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Digital transformation in village governance has encouraged Village-Owned Enterprises (Badan Usaha Milik Desa or BUMDes) to adopt information technology-based systems to improve the effectiveness of business management and public service delivery. One such innovation is the Sugihwaras Electronic BUMDes (e-BES) application, developed by the